Medication errors in elderly people: contributing factors and future perspectives - Fialová, Daniela; Onder, Graziano (British journal of clinical pharmacology, 2009)
1. Older people have substantial interindividual variability in health, disability, age-related changes, polymorbidity, and associated polypharmacy, making generalization of prescribing recommendations difficult. 2. Medication use in older adults is often inappropriate and erroneous, partly because of the complexities of prescribing and partly because of many patient, provider, and health system factors that substantially influence the therapeutic value of medications in aged people. 3. A high prevalence of medication errors in older adults results on the one hand from accumulation of factors that contribute to medication errors in all age groups, such as polypharmacy, polymorbidity, enrollment in several disease-management programmes, and fragmentation of care. On the other hand, specific geriatric aspects play a role in these medication errors; these include age-related pharmacological changes, lack of specific evidence on the efficacy and safety of medications, underuse of comprehensive geriatric assessment, less availability of drug formulations offering geriatric doses, and inadequate harmonization of geriatric recommendations across Europe. 4. The dearth of geriatric clinical pharmacology and clinical pharmacy services compounds the difficulties. 5. There are gaps in research and clinical practice that lead to frequent medication errors in older adults, which must be solved by future studies and by regulatory measures in order to support errorless and appropriate use medications in these people.
Keywords: lidé; Medication Errors; Decision Making; Risk Factors; Drug Prescriptions; polypharmacy; lékové předpisy; lékařská praxe - způsoby provádění; Humans; Geriatric Assessment; Practice Patterns, Physicians'; geriatrické hodnocení; Aged, 80 and over; senioři nad 80 let; Aged; medikační omyly; rozhodování; Polypharmacy; rizikové faktory; senioři